M. Jońca, W.S. Staszewski, Łacina w prawie międzynarodowym. Pojęcia i wyrażenia, Wydawnictwo Werset, Lublin 2024, ISBN 978-83-813-5309-0, ss. 168 - Stodulska, Irmina Weronika (Zeszyty Prawnicze, 2025)
.